On the Brink of Virtual Extinction: Hunting and Killing Animals in Open World Video Games - van Ooijen, Erik (Eludamos: Journal for Computer Game Culture, 2018)
<!--[if gte mso 9]> <![endif]--> The article focuses on the underlying structures evaluating acts of violence against different bodies in games. Taking the hunting mechanics of open-world games as its point of discussion, it looks at how game design manifests procedural arguments on the ideological aspects of animal violence. Whereas there are instances of explicit violence in these games, the article argues that the explicitness of such depictions serves to emphasize the “messiness” of producing animal goods, thus impeding the “carnist” ideological view of meat as pure commodity. By considering how games distinguish humans from animals, it looks at what violent acts are rendered acceptable or unacceptable, and notes distinctions between what bodies are protected by, or exempt from, moral and legal rights. Finally, the article considers how the algorithmic nature of spawning makes digital animals immune to extinction. Interestingly enough, the article nevertheless notices how a game may intentionally diverge from this logic in order to defamiliarize its established logic. Among the games discussed are Rockstar’s Red Dead Redemption (2010), and Ubisoft’s Assassin’s Creed III (2012) and Far Cry 3 (2012). <!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->